Efficient photocatalytic degradation of brilliant green using Sr-doped TiO2 nanoparticles - Sood S.; Umar A.; Kumar Mehta S.; Sinha A.S.K.; Kansal S.K. (My University, 2025)
Strontium doped TiO2 nanoparticles have been successfully synthesized by an ultrasonic-hydrothermal method and post calcination treatments. The synthesized catalyst has been characterized in details using X-ray diffraction (XRD), transmission electron microscopy (TEM), Brunauer Emmett-Teller (BET) surface area analyzer, thermogravimetric analysis (TGA), Fourier transform infrared (FT-IR), XPS (X-ray photoelectron spectroscopy) and photoluminescence (PL) spectroscopy. Sr-doped TiO2 catalyst has been further investigated as an efficient photocatalyst for the degradation of a triarylmethane dye, Brilliant Green. Excellent degradation efficiency of 96% was achieved within 60 min of photocatalytic reaction using the synthesized nanoparticles. It has been concluded that doping TiO2 with strontium ions caused inhibition of recombination of photogenerated charge carriers, leading to high quantum efficiency. © 2014 Elsevier Ltd and Techna Group S.r.l.